FCRを用いたマンモグラフィシステム専用品質管理 ツールとしての1Shot Phantomの評価 - 長島, 千恵子; 森山, 紀之; 小林, 宏之; 内山, 菜智子; 早乙女, 滋; 田木, 正浩; 楠木, 哲郎; 永田, 実緒; 三小田, 勝博 (日本放射線技術学会雑誌, 2009)
Currently daily quality control (QC) tests for mammography systems are generally evaluated by using visual analysis phantoms, which of course means subjective measurement. In our study, however, we evaluated a novel digital phantom, the 1Shot Phantom M plus (1Shot Phantom), together with automatic analysis software dedicated for mammography systems using Fuji computed radiography (FCR). The digital phantom enables objective evaluation by providing for actual physical measurement rather than subjective visual assessment. We measured 1) contrast to noise ratio (CNR), 2) image receptor homogeneity, 3) missed tissue at chest wall side, 4) modulation transfer function (MTF), and 5) geometric distortion utilizing the 1Shot Phantom. We then compared the values obtained using the 1Shot Phantom with values obtained from the European guidelines and International Electrotechnical Commission (IEC) standards. In addition, we evaluated the convenience of using the digital phantom. The values utilizing the 1Shot Phantom and those from the European guidelines and IEC standards were consistent, but the QC tests for the European guidelines and IEC standards methods took about six hours while the same QC tests using the 1Shot Phantom took 10 minutes or less including exposure of the phantom image, measurement, and analysis. In conclusion, the digital phantom and dedicated software proved very useful and produced improved analysis for mammography systems using FCR in clinical daily QC testing because of their objectivity and substantial time-saving convenience.